2012
DOI: 10.1007/s00347-011-2460-4
|View full text |Cite
|
Sign up to set email alerts
|

Einfluss des Geburtsmodus auf vorbestehende Augenerkrankungen

Abstract: Many ophthalmologists and obstetricians recommend either an assisted vaginal delivery with forceps or vacuum extraction, or a Caesarean section in cases of pre-existing eye diseases, such as myopia, retinal detachment, glaucoma or diabetic retinopathy. This is mainly based on the increase of intraocular pressure during the final stage of labor. These recommendations, however, are not evidence-based. None of the published trials have reported any retinal changes after vaginal delivery. This report provides info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Recommendations regarding delivery methods in women with pre-existing ocular disease are not evidencebased (40). The question whether a caesarean section should be performed for ophthalmological reasons is most commonly asked, in the authors' experience, in cases of glaucoma, myopia, peripheral retinal degeneration, and status post retinal detachment.…”
Section: Methods Of Deliverymentioning
confidence: 99%
“…Recommendations regarding delivery methods in women with pre-existing ocular disease are not evidencebased (40). The question whether a caesarean section should be performed for ophthalmological reasons is most commonly asked, in the authors' experience, in cases of glaucoma, myopia, peripheral retinal degeneration, and status post retinal detachment.…”
Section: Methods Of Deliverymentioning
confidence: 99%
“…It is thought that the acute increase in intraocular pressure and decrease in ocular perfusion related to the valsalva maneuver during vaginal delivery can cause optic nerve damage in glaucoma patients [12]. Cesarean section is recommended for patients with high grades of myopia or retinal degeneration based on the thought that vaginal delivery can trigger retinal detachment [13,14]. In the studies of Sochaet al and in our study, the most frequent cesarean indications are myopia and retinaldetachment.…”
Section: Discussionmentioning
confidence: 53%
“…In the studies of Sochaet al and in our study, the most frequent cesarean indications are myopia and retinaldetachment. However, there are no evident-based reports in the literature indicating that vaginal delivery is associated with retinal detachment or progression of glaucoma [13,14]. Animal experiments, observational and comparative studies covering the pre-and post-delivery periods in pregnant individuals with ophthalmologic diseases are required.…”
Section: Discussionmentioning
confidence: 99%
“…These recommendations, however, are not evidence-based (21) . As far as we know, there are not so many published trials that have reported any significant adverse retinal changes after vaginal delivery, therefore preexisting eye disease is not an indication for instrumental or operative delivery (22) .…”
Section: Natural Vaginal Delivery or Cesarean Section For Myopic Women?mentioning
confidence: 95%